A version of a story (2013)
Ok, Doctor. I am going to tell you the reason why I am here today. A couple of weeks ago I hung out with some girls. We went to have some beers in a bar. It was an ok bar and so was the music. The only bad thing that happened, apparently I mean, was the fact that I did not share the taxi ride after leaving. Well, one of the girls did not ride in the cab either. As that was the issue, I still don’t know what the trouble was. Both of us, left behindon a rainy and chilly night. The rain made the street more romantic. All the neon lights reflected on the wet pavement created that scene of a New York street, or any big city, similar to the ones seen in the movies, wherelovers go for a walk. And the cold weather was inviting to… Oh God!, that night was exactly perfect to be spent with someone else…